Microwave-Assisted Synthesis and Antimicrobial Activity of Some Novel Isatin Schiff Bases Linked to Nicotinic Acid via Certain Amino Acid Bridge - Ahmed M. Naglah; Hassan M. Awad; Mashooq A. Bhat; Mohamed A. Al-Omar; Abd El-Galil E. Amr (Journal of Chemistry)
The coupling reaction of nicotinic acid with certain L-amino acid methyl esters including valine, leucine, and phenylalanine was done by the use of acid chloride method. The products were reacted with hydrazine hydrate 99% to give the corresponding hydrazides that were reacted with indoline-2,3-dione (isatin) to get Schiff bases under the application of microwave irradiation technique. These novel compounds were characterized by means of their FT-IR, 1H NMR, and mass spectral data. Additionally, the specific optical rotation and elemental analysis were measured. The in vitro antimicrobial activity of the synthesized compounds was evaluated by agar diffusion method. The compounds showed a strong antimicrobial inhibitory activity. Most of the test compounds possessed a broad spectrum of activities having MIC values ranging from 50 µg/mL to 500 µg/mL.